Watching Photos in Shatila: Visualizing Politics in the 2011 March of Return. Issue 3 (26th May 2016) - Allan, Diana K.
Abstract : This article focuses on the 2011 March of Return in Lebanon and explores the epistemic gap between image and event, examining how nationalist iconography of the Israel–Palestine conflict informs and distorts popular understanding of the political concerns of refugees. News outlets and social media distilled the march's political symbolism into one of determination and resolve, with refugee claims directed exclusively at Israel. Camp discussions meanwhile revealed fractured and equivocal motives, including sharp if variously veiled critiques of the Palestinian factions, the Shia political party Hezbollah, and the Lebanese State. Local debates about representation—about the production, dissemination, and interpretation of political images—are significant in their skepticism about the democratizing effects of social media, and in their suggestiveness about emergent forms of political life and aspiration for which no visual grammar yet exists.